2008
DOI: 10.1302/0301-620x.90b2.19950
|View full text |Cite
|
Sign up to set email alerts
|

The use of ultrasound in acquisition of the anterior pelvic plane in computer-assisted total hip replacement

Abstract: We have evaluated in vitro the accuracy of percutaneous and ultrasound registration as measured in terms of errors in rotation and version relative to the bony anterior pelvic plane in computer-assisted total hip replacement, and analysed the intra- and inter-observer reliability of manual or ultrasound registration. Four clinicians were asked to perform registration of the landmarks of the anterior pelvic plane on two cadavers. Registration was performed under four different conditions of acquisition. Errors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
(68 reference statements)
0
32
1
Order By: Relevance
“…As mentioned by Dr. Leopold in his Editor's Spotlight [5], we can either perform prospective randomized studies powered for a particular goal or do larger studies with less robust study design and larger sample size. These limitations have been clearly outlined in our paper [9].…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…As mentioned by Dr. Leopold in his Editor's Spotlight [5], we can either perform prospective randomized studies powered for a particular goal or do larger studies with less robust study design and larger sample size. These limitations have been clearly outlined in our paper [9].…”
mentioning
confidence: 74%
“…But the acquisition of this plane is done percutaneously during the surgery [7,8]. In a previous cadaveric study [9], we demonstrated that the percutaneous acquisition in patients who are obese may lead to more than 10°of inaccuracy on the final cup anteversion. This variance is likely due to the difference of the soft-tissue thickness between the iliac spines and the symphysis in patients who are obese [9].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This procedure remains an important source of inaccuracy in imageless navigation systems. In a previous cadaver study different conditions of landmark acquisition were investigated [18]. Percutaneous registration methods with and without draping showed a significant error in cup anteversion but not in inclination.…”
Section: Discussionmentioning
confidence: 99%
“…The results in this study suggest that the bias regarding anteversion could be avoided by applying a semi-invasive registration technique by puncturing the skin to obtain bony contact to the pubic bone near the pubic tubercles. Alternatively, ultrasound acquisition of the ASIS might be helpful [18].…”
Section: Discussionmentioning
confidence: 99%